2022
DOI: 10.1523/jneurosci.0859-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Social: A Neural Signature for Conscious Perception of Social Interactions

Abstract: Social information is some of the most ambiguous content we encounter in our daily lives, yet in experimental contexts, percepts of social interactions—that is, whether an interaction is present and if so, the nature of that interaction—are often dichotomized as correct or incorrect based on experimenter-assigned labels. Here, we investigated the behavioral and neural correlates of subjective (or conscious) social perception using data from the Human Connectome Project in which participants (n= 1049; 486 men, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Nonetheless, we note that infants have face-selective responses in STS. In both infants and adults, face responses in STS are thought to be multi-modal -integrating across visual and auditory domains (112)(113)(114)(115). At every age measured, there is a region in the STS responds more to faces than non-face object categories (116,117).…”
Section: Face-selective Responses In Ios and Sts Of Infants' Brainsmentioning
confidence: 99%
“…Nonetheless, we note that infants have face-selective responses in STS. In both infants and adults, face responses in STS are thought to be multi-modal -integrating across visual and auditory domains (112)(113)(114)(115). At every age measured, there is a region in the STS responds more to faces than non-face object categories (116,117).…”
Section: Face-selective Responses In Ios and Sts Of Infants' Brainsmentioning
confidence: 99%
“…If real TMS decreased the participants' ability to distinguish between the communicative and individual gestures (i.e., creating a situation of uncertainty) and biased them into mistaking individual for communicative ones, then that might explain why participants made more false alarms following real TMS (especially in the individual condition). In line with this reasoning, it has been shown that social judgements like emotion identification are adversely affected by uncertainty (Clarke et al, 2005) and that perceptual ambiguity can be associated with a bias towards social interpretations (Salge et al, 2020;Varrier & Finn, 2022). The opposite effect, however, can sometimes be observed as well (Vanrie et al, 2004).…”
Section: Real Tms Leads To An Increase Rather Than a Decrease In Fals...mentioning
confidence: 91%
“…Similar to the idea that participants may vary in their level of interest in experimenterdesigned stimuli, previous work has shown that researcher labels of stimuli do not always capture participants' subjective experiences of those stimuli, and that using participants' own reports rather than experimenter labels can explain more variance in brain activity 57 . Just as there is widespread awareness of (and analytical techniques to account for) individual differences in the functional organization of the human brain 29,58 , these results suggest that there should be a similar acknowledgement of individual differences in how participants subjectively experience experimental stimuli in neuroimaging studies.…”
Section: Personalizing Narratives To the Individual Reveals Unexpecte...mentioning
confidence: 99%